Electrodeposition of hydroxyapatite/functionalized carbon nanotubes (HAp/fCNTs) coatings on the surface of 316L stainless steel - Thom, Nguyen Thi; Nam, Pham Thi; Phuong, Nguyen Thu; Hong, Cao Thi; Trang, Nguyen Van; Xuyen, Nguyen Thi; Mai Thanh, Dinh Thi (Vietnam Journal of Science and Technology, 2017)
The coatings of hydroxyapatite/functionalized carbon nanotubes (HAp/fCNTs) were successfully synthesized on the surface of 316L stainless steel (316L SS) by electrodeposition. To improve the dispersion of CNTs into the electrolyte, CNTs were functionalized in the mixture of 67 % HNO3 and 98 % H2SO4 before electrodeposition coatings to form fCNTs. Different amounts of fCNTs were incorporated into the apatite coatings by adding fCNTs into the electrolyte solution. In this study, Fourier Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Thermal Gravimetric Analysis (TGA) and mechanical techniques were used to analyze characteristic of fCNTs and the HAp/fCNTs coatings. The FTIR spectra of CNTs before and after acid treated process show that CNTs are functionalized by chemically method with carboxylic acid groups (–COOH) on their surface. The SEM images confirm that the functionalized process by the acid mixture does not change the morphology of CNTs. The nanocomposite coatings contain single phase of HAp and CNTs with the coating thickness of 6.9 µm and the amount of fCNTs in the coatings is 7.25 %. With 0.5 g/L of fCNTs in the electrolyte solution, the solubility of the coating decreases in comparision with pure HAp coatings.